Thionamides-Related Vasculitis in Autoimmune Thyroid Disorders: Review of Current Literature and Case Reports - Romeo, Elisabetta L.; Russo, Giuseppina T.; Giandalia, Annalisa; Villari, Provvidenza; Mirto, Angela A.; Cucinotta, Mariapaola; Perdichizzi, Giuseppa; Cucinotta, Domenico (IntechOpen, 2011)
None